Cracking behaviour, failure modes and lifetime analysis of M320 abradable compressor seal coating - Goergen, Sandra (Cranfield University, 2012)
Metco 320 is a AlSi-hBN-polyester abradable, used in the high pressure compressor of commercial gas turbines. The material response to cyclic heating and cooling, and the resulting changes in microstructure, as well as their associated failure mechanisms were investigated. It was found that the top surface layer of the abradable liner degrades over its lifetime. During thermal cycling hBN is removed from the material’s microstructure, which results in the degradation of the abradable and increased brittleness of the top surface. Furthermore, material cracking and delamination behaviour during service was successfully reproduced in the laboratory. The cracking and delamination observations made during overhaul, were replicated using cyclic water-quenching, but the spallation of abradable material did not occur. Investigations into material properties and their influence upon the abradable failure mechanics revealed, that soft M320 matched the observations made during engine overhauls. It could also be established, that the plasma spray process, grit blasting, surface treatment after deposition and the transient of the substrate affect the abradable’s performance and life-time, when heat cycled. Some service casings suffer from premature liner loss. These unscheduled overhauls are costly and their number is desired to be reduced, if possible eliminated. In order to control the material failures, the stresses introduced into the abradable seal during manufacturing need to be reduced, since this is one of main drivers for material cracking and delamination. Furthermore, it was established, that material at the top end of the hardness specification performed better in service. This is due to the fact, that more AlSi metal matrix is present in the microstructure and the hBN loss does not affect the material integrity as much as in soft material. 2D and 3D modelling showed temperature and strain profiles evolving during the quenching process. These show the areas of high strain, which are consistent with the crack initiation areas observed during testing. It can be concluded, that M320 abradable is a very complex material system, which is influenced by several parameters. This research project highlighted, how sensitive the failure modes are to changes in the material/substrate combination. Recommended is to increase the material hardness towards the upper end of the current specification (70 HR15Y), reduce the stresses in the substrate and the abradable material by means of annealing stages after grit blasting, and temperature control during plasma spraying. Furthermore, it would be beneficial to reduce the machining of the abradable’s surface after deposition, as well as carrying out further research into the failure modes of abradables.